INVESTIGATING EFL LECTURERS' PERCEPTION AND STRATEGIES IN ENHANCING EFFECTIVE ENGLISH LANGUAGE TEACHING: A CASE STUDY - Rasmin , La Ode; Samsudin , Samsudin; Isma , Adi (Universitas Muhammadiyah Prof. DR. HAMKA, 2023)
Teaching English as a Foreign Language (TEFL) needs a strategy and an approach to enhance the effective teaching process. This research aims to gain deeper insight into effective methods of teaching English as a foreign language (EFL) in a university context. This study used case study research involving structured interviews via Google form with four EFL lecturers at Universitas Muslim Buton, Baubau, Southeast Sulawesi. The data in this study used a thematic analysis. The results of this study reveal a rich understanding of the views and teaching strategies used by EFL lecturers. In interviews, the lecturers outlined teaching approaches they believed were effective in improving students' English language skills, how they select the learning materials and the challenges and adjustments in teaching. This study found that the EFL lecturers use communication-based techniques and the contextual approach in choosing the materials learning to enhance classroom practice. In addition, this research also identifies the challenges EFL lecturers face in implementing these teaching practices and creating an effective learning environment. It is hoped that the results of this research will provide valuable guidance for developing training programs and improving EFL teaching practices in university settings. Keywords: EFL Lecturer, Perceptions and Strategies, Effective Teaching